Vascular risk and neuroimaging profile of MCI patients in the FINOMAIN Study: Neuroimaging / multi‐modal comparisons. (7th December 2020) - Guevarra, Anne Cristine Deocariza; De Guzman, Maria Fe Payno; Galvez, Francy Joy; Rodriguez, Anthony; Citron, Raphael Louis B; Yu, Justine Megan F; Rivamonte, Vladimir; Phung, Thien Kieu Thi; Dominguez, Jacqueline C
Abstract: Background: The Asian population has been found to be at a higher risk of developing dementia compared to other races due to the high prevalence of vascular risk factors. Utilization of different modalities that manage these vascular risk factors is the focus of this study in order to prevent progression of dementia among senior citizens with mild cognitive impairment. Method: Community‐based participants with MCI were recruited to join the FINOMAIN Study. They were divided into control and intervention groups, to which INDAK (dance therapy) shall be given. Both groups shall receive health education, management of non‐communicable diseases, and nutrition management. 72 participants shall undergo neuroimaging. Hypertension, diabetes mellitus type 2, and dyslipidemia were derived from clinical data and ancillary procedures. Small vessel disease markers (white matter hyperintensity, chronic lacunes, enlarged perivascular spaces, global atrophy, medial temporal lobe atrophy, frontotemporal atrophy, and posterior cortical atrophy) were documented through T1W, T2W, and FLAIR sequences on MRI and with the use scales like Fazekas, modified Staal's score, and atrophy scores. All MRI assessments were performed by a single neurologist blinded to the clinical and cognitive measures. Cognitive measures had been done including tests for global cognition (MMSE‐P and MoCA‐P). Independent t‐test was used to show descriptive results of both groups. Result: 42 subjects had completed MRI as of this writing (18 control group, 24 intervention group) with a mean age of 70 and mean years of education 9.48 years. Only 12% of the subpopulation are males. Markers of noncommunicable diseases did not show significant differences between groups. SVD burden measured through modified Staal's score showed 2.50+ 0.985 for the control group and 2.33+ 0.917 for the intervention group (with a maximum score of 3 points) Fazekas scores for both groups showed moderate WMH burden (2.17+ 0.786 vs. 2.29+ 0.859; p = 0.125). MTA scores did not exceed the score of 2 in both groups (1.56+ 0.784 vs. 1.50+ 0.590; p = 0.794). Conclusion: The subsample of the FINOMAIN study shows comparable demographics, clinical, and neuroimaging findings which is considered as a good pre‐intervention data. Small vessel disease burden in the neuroimaging is quite high in both study groups.